THE INFLUENCES OF FINANCIAL LITERACY AND FINANCIAL TECHNOLOGY ON MANADO MILLENNIAL INVESTMENT INTENTION IN CAPITAL MARKET - Elsa Mussy; Willem J. F. A. Tumbuan; Maria V. J. Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
The development of FinTech and Financial Literacy for the younger generation has been very developed in the digital era, at the same time investment is also important for economic development for the welfare of the community, but because of the risks that can be caused when making investments, it is necessary to have knowledge about financial literacy. For this reason, the author will conduct a study on how FinTech and Financial Literacy affect the intention to invest in millennial. This study aims to determine: (1) the influence of Financial Literacy on Manado millennial investment intention on Capital Market. (2) The influence of Financial Technology on Manado Millennial investment intention on Capital Market. (3) The influence of Financial Literacy and Financial Technology on Manado Millennial investment intention on Capital Market. This study uses a quantitative method with a correlational approach, the population and sample in this study will be determined by the Slovin formula. Slovin's formula can be very precise in situations with large populations such as in this study. The sample that will be used is 100 people from the millennial generation. The criteria are between 22 – 42 years old, namely millennial in Manado who already have financial literacy and know about the capital market.   Keywords: financial literacy, financial technology, investment intention.